2004
DOI: 10.1002/jbm.a.30002
|View full text |Cite
|
Sign up to set email alerts
|

Poly(carbonate urethane) and poly(ether urethane) biodegradation: In vivo studies

Abstract: Several strategies have been used to increase the biostability of medical-grade polyurethanes while maintaining biocompatibility and mechanical properties. One approach is to chemically modify or replace the susceptible soft segment. Currently, poly(carbonate urethanes) (PCUs) are being evaluated as a replacement of poly(ether urethanes) (PEUs) in medical devices because of the increased oxidative stability of the polycarbonate soft segment. Preliminary in vivo and in vitro studies have reported improved biost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
151
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 170 publications
(168 citation statements)
references
References 25 publications
15
151
2
Order By: Relevance
“…Biostability of the retrieved Dynesys spacers was suggested in the IR results, particularly due to an absence of peaks at 1,650 and 1,174 cm -1 (Fig. 6), which would be attributed to the biodegradation process and products if present [8]. Table 3 shows that any as-characterized chemical changes were minor and limited to the PCU surfaces at the 5% systematic detection limit of the FTIR spectrometer and that nearly no changes occurred below the surface of PCU spacers.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Biostability of the retrieved Dynesys spacers was suggested in the IR results, particularly due to an absence of peaks at 1,650 and 1,174 cm -1 (Fig. 6), which would be attributed to the biodegradation process and products if present [8]. Table 3 shows that any as-characterized chemical changes were minor and limited to the PCU surfaces at the 5% systematic detection limit of the FTIR spectrometer and that nearly no changes occurred below the surface of PCU spacers.…”
Section: Discussionmentioning
confidence: 93%
“…Christenson et al [8] reported that PCU 80A was susceptible to biodegradation after implantation for 20 weeks in a rat model. In comparison with the PCU material used in Dynesys, PCU 80A has a different hard-soft segment ratio and molecular weights.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations